The Effects of the China shock on the brazilian agriculture - Carreira, Igor Antônio Araújo (2020)
This study examines the effects of a commodities’ trade shock on the agricultural sector. I estimate the impacts of the increased Chinese demand for commodities on land use, technology adoption and agricultural productivity in Brazil. Using municipality-level data from the Brazilian Agricultural Census, I identify the effects of the increased export demand from China on local agricultural outcomes with a shift-share instrument. I find that municipalities more exposed to the Chinese demand growth experienced a persistently higher conversion of pasture to cropland and a larger concentration of land ownership than municipalities less exposed. I find no significant effect on the expansion of farmland area. Additionally, these municipalities faced a lower increase in the use of agricultural inputs and a long-term rise on cattle ranching productivity, relative to regions less specialized in the production of commodities demanded by China.